2007
DOI: 10.1111/j.1365-2699.2007.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant attributes determining the regional abundance of weeds on central European arable land

Abstract: Aim  Several recent studies have aimed to identify the biological, ecological and distributional attributes that determine the regional abundance of plant species. Here we aim to assess the relationships between regional abundance and species attributes in weeds on arable land. Location  Czech Republic, central Europe. Methods  The relationships between regional abundance and species attributes were studied with a data set of 381 weed species occurring on arable land in the Czech Republic. Regional species abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 46 publications
3
49
0
1
Order By: Relevance
“…Study by Lososova et al (2008) showed that the list of most abundant weeds in the Czech Republic corresponds very well to the lists of other countries of Central and Northern Europe and includes some species problematic for hemp: Polygonum aviculare, F. convolvulus, C. album can be found on agricultural fields throughout Europe independently of climatic conditions. Hyvonen et al (2011) suggest that weed species richness and abundance depend on land use type and region and tend to decline from fallows and low-input to conventionally cultivated land use type and from south to north.…”
Section: Introductionmentioning
confidence: 73%
“…Study by Lososova et al (2008) showed that the list of most abundant weeds in the Czech Republic corresponds very well to the lists of other countries of Central and Northern Europe and includes some species problematic for hemp: Polygonum aviculare, F. convolvulus, C. album can be found on agricultural fields throughout Europe independently of climatic conditions. Hyvonen et al (2011) suggest that weed species richness and abundance depend on land use type and region and tend to decline from fallows and low-input to conventionally cultivated land use type and from south to north.…”
Section: Introductionmentioning
confidence: 73%
“…It shows a decreasing abundance and diversity of weeds from the beginning of wide applications of herbicides and levelling of site conditions until the 1980s but often increasing weed abundances during the last two decades due to herbicide reduction programmes, structural changes and a partial reversal of intensification (Andreasen et al 1996;Hyvönen et al 2003;Miloanova et al 2007;Kapeluszny and Haliniarz 2007;Novák et al 2009). However, this increase is rarely related to weed species of conservational value but usually involves higher proportions of problematic perennial and monocotyledonous species (Hyvönen et al 2003;Novák et al 2009;Potts et al 2010;Pinke et al 2011), higher abundances of generalist species that are common in all crops (Fried et al 2010), nitrophilous weeds and weeds adapted to dense vegetation stands (Lososová et al 2008;Šilc et al 2009;Májeková et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A lokális tényezők fontosak voltak az életformák, növekedési formák és megporzási módok szempontjából, míg a táj komplexitása elsősorban a széllel terjedő fajok részesedését befolyásolta. Lososová et al (2008) megállapították, hogy Közép-Európában a leggyakoribb szántóföldi gyomfajok a következő jellegekkel rendelkeznek: korán virágoznak, alkalmazkodtak az alacsony hőmérséklethez, viszonylagosan árnyék-tűrők és magas a tápanyagigényük. Ezzel szemben Storkey et al (2010) "ritka gyomnövény jelleg szindrómaként" azonosították a következő tulajdonságokat: alacsony termet, nagyméretű mag és késői virágzás (pl.…”
Section: Funkciós Megközelítésunclassified